Pandemi Covid-19 Sebagai Bentuk Overmacht Terhadap Pelaksanaan Perjanjian Kredit Di Perbankan - Sherlin Sherlin; Lu Sudirman (Widya Yuridika, 2021)
At the end of 2019, the world's first discovery of a highly contagious and rapidly growing virus called the Covid-19 virus. In legal terms, it is known as overmacht which means a forced state. The Covid-19 virus pandemic has grown rapidly since the beginning of 2019 until now. The biggest impact of the Covid-19 virus pandemic is the world economy. When it comes to the economy, the most influential field is banking. In the banking world, which provides loan services to customers, of course, it has had a big impact since the Covid-19 virus pandemic. Therefore, this paper aims to discuss the legal consequences of the overmacht condition in the banking sector, especially on the implementation of credit agreements in banking. The method used in this paper is normative law using a statutory approach, namely POJK and the Civil Code which contains the topic of discussion with secondary data types. With the overmacht condition, OJK as the authorized party issued a new POJK regulation regarding the implementation of credit in banking during this pandemic. Where overall the contents and provisions of the POJK are in accordance with applicable law, by emphasizing on the banking sector to continue to apply the precautionary principle in providing relaxation as an effort to relieve loans or debtor customer credit so that credit activities in banking remain organized and run well.